The Urgency of Legal Profession Regulation Amidst The Integration of Artificial Intelligence - Andry Setiawan; Rindia Fanny Kusumaningtyas; Afifah Widyastuti; Ibadurrahman Hanan Abdullah (Universitas Negeri Semarang, 2025)
Artificial Intelligence (AI) is reshaping the legal profession by enhancing research speed, document review, and case analysis. Yet, its integration also raises pressing concerns over accountability, data privacy, and ethical standards. This study addresses the research problem: How should Indonesia regulate AI in law to balance innovation with justice and human rights? Three guiding questions inform the analysis: (1) What is the extent of AI adoption by Indonesian legal practitioners? (2) What legal and ethical risks arise? (3) What regulatory responses are most suitable for Indonesia’s plural legal context? Adopting a socio-legal methodology, data were collected through literature review, in-depth interviews, and an online survey of 102 practitioners. Findings show that 38% of respondents currently use AI tools, mainly for legal drafting and research, but skepticism persists. Advocates in Semarang reported errors in AI-generated contracts, illustrating unresolved accountability gaps under existing laws. Judges highlighted risks of bias and opacity if AI expands into case management without safeguards. The novelty of this research lies in its empirical evidence: it is the first Indonesian study to combine practitioner perspectives with regulatory analysis, moving beyond conceptual debates. By linking adoption patterns to deficiencies in the ITE Law, PDP Law, and PERMA No. 1/2019, the study reveals concrete vulnerabilities in legal practice. The study concludes that interim sectoral measures such as PERADI guidelines and judicial ethics updates are urgently needed while developing a comprehensive AI law. Responsible governance is essential to ensure AI strengthens, rather than undermines, fairness, transparency, and the rule of law.